Plasmid-determined immunity of Escherichia coli K-12 to colicin Ia Is mediated by a plasmid-encoded membrane protein. - Weaver, C A (1981)
The colicin Ia structural (cia) and immunity (iia) genes of plasmid pColIa-CA53 have been cloned into the cloning vector pBR322. These two genes are closely linked, and both of them can be isolated on a deoxyribonucleic acid fragment approximately 4,800 base pairs long. An analysis of the polypeptides synthesized in ultraviolet-irradiated cells containing these cloned genes led to the conclusion that the iia gene product is a polypeptide with a molecular weight of approximately 14,500. Insertion of transposon Tn5 into the iia gene led to a concomitant loss of the immune phenotype and the ability to produce this protein. Fractionation of ultraviolet-irradiated cells harboring a plasmid carrying the iia gene showed that the immunity protein is a component of the inner (cytoplasmic) membrane. Furthermore, the mechanism of immunity to colicin Ia appears to operate at the level of the cytoplasmic membrane. This conclusion is based on our finding that membrane vesicles prepared from colicin Ia-immune cells could be depolarized by colicins E1 and Ib but not by colicin Ia.